Anne Frank remembered [videorecording (DVD)] - Blair, Jon; Blair, Jon; Blair, Jon; Branagh, Kenneth; Close, Glenn, 1947-; Gies, Miep, 1909-2010; Frank, Anne, 1929-1945 (Columbia TriStar Home Entertainment, 2004)
Features vintage newsreel footage, photographs and a rare home movie to look beyond the celebrated pages of Anne Frank's diary. Includes interviews with her friends, family and protector, Miep Gies.